2014
DOI: 10.5851/kosfa.2014.34.6.792
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Channel and Microbial Characteristics of Pig By-products in Korea

Abstract: The distribution channel of meat by-products from the pig farm to the final consumer can include a meat processor, wholesale market, wholesaler, retailer, and butcher shop. Bacterial contamination at any of these steps remains to be a serious public health concern. The aim of this study was to evaluate the distribution channel and microbial characteristics of pig by-products in Korea. Upon evaluation of pig by-products in cold storage, we found that the small and large intestine were significantly (p<0.05) hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Therefore, the VP method seemed to be more effective in maintaining the pH environment of small intestine during cold distribution. Kang et al (2014) demonstrated that after 7 d of cold storage, pH levels of white viscera with small and large intestine were favorable for microbial growth. From this reason, the small intestine requires a more careful washing process than the other pork by-products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the VP method seemed to be more effective in maintaining the pH environment of small intestine during cold distribution. Kang et al (2014) demonstrated that after 7 d of cold storage, pH levels of white viscera with small and large intestine were favorable for microbial growth. From this reason, the small intestine requires a more careful washing process than the other pork by-products.…”
Section: Resultsmentioning
confidence: 99%
“…The freezing of liver, kidney, and heart for 4 d did not significantly decrease the bacterial counts in these products (Hanna et al, 1982). Kang et al (2014) suggested that small intestine is required a lot of washing times to remove blood, indigestible feed, and feces, etc. These authors have demonstrated that the reduction of initially high bacterial numbers is very important for shelf-life extension and freshness maintenance of pig small intestine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pork by-products include blood, bone, skin, feet, tail, red internal organs (liver, lung, heart, and kidney), white internal organs (large and small intestine), and head. By-product can provide energy, proteins, minerals, and vitamins required for human health ( Kang et al , 2014 ; Seong et al , 2014 ). However, by-products are underutilized with low price because they are regarded as inferior protein source ( Kim et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%